Decarbonising cities: certifying carbon reduction in urban development - Rauland, Vanessa (Curtin University, 2013)
There are many outstanding examples of carbon neutral, zero carbon and other forms of low carbon cities, districts and urban development around the world, which have demonstrated the vast potential for carbon abatement within the built environment. However, these concepts and approaches have not yet become mainstream. Furthermore, how each city or development defines its carbon claim, including how emissions are calculated and goals are achieved (for example, if offsets are used) varies considerably. This makes comparisons difficult, claims less meaningful and replication challenging. It also leads to concern around false carbon claims and ‘greenwashing’.Although carbon certification is now widely adopted as a voluntary carbon market instrument for a variety of sectors, it has not yet been applied to urban development. This research therefore examines the implications of certifying carbon reductions within this sector. A framework is proposed, which includes a standardised approach to quantifying emissions at the precinct-scale and five core elements that would need to be considered when certifying urban development.It is argued that certification can help to acknowledge and reward progressive developers, increase the credibility of carbon claims within the built environment and help to provide benchmarks and baselines for the sector. Certification could also become a mechanism by which a variety of incentives can be offered to developers to encourage greater uptake of low carbon design. It is expected that a combination of factors – a standard approach to quantifying emissions, carbon certification and the provision of incentives – can help to mainstream this type of development, which will be essential in addressing many global challenges such as climate change and resource depletion.